HUBUNGAN PENGETAHUAN IBU TENTANG JAJANAN YANG MENGANDUNG ZAT KIMIA BERBAHAYA DENGAN PERILAKU JAJAN ANAK - Kosasih, Ikhwan; Firsada, Firsada (Jurnal AKP, 2012)
Food has an important role to fulfill the energy and nutrition of pre-school age children, but the safety of food is still unsave. Using other strange food like aspartame and MSG by producer makes the safety and quality of food is very low and so the food consumed by child need more special intention for parent. The purpose from the research is identifying the correlation of motherâs knowledge about dangerous chemical food to child behavior at pre school.Design research used is Cross Sectional. The items wewe 47 respondents with full of inclusion and exclusion. Taking an item uses Simple Random Sampling.From the research, we found mother knowing is Good : 28 respondents (59,57%) and child food behavior at pre school is health with 41 respondents (87,23%). From the result Coeffisien contingency test, we get significant score 0,035 < 0,05 means Ho refuses. It means there is correlation motherâs klowledge about dangerous chemical food to child behavior at pre school with low quality.Motherâs knowledge about dangerous chemical food to child behavior at pre school enriches knowledge, information and gives control an intention to food child behavior. A mother should intent food child behavior in other that it is controlled to be health child food behavior.